Penerapan Model Pembelajaran Giving Question and Getting Answer Terhadap Kemampuan Komunikasi Matematis Siswa - Asep Sujana; Rika Cahyawati (Universitas Serang Raya, 2018)
The research aims to analyse the students pre-ability, post-ability, and improvement of mathematical communication ability towards Giving Question and Getting Answer technique. The research is conducted in SMP Negeri 1 Cinangka academic year 2017/2018. The research method is quasi-experiment with pretest and posttest control group design. The research sample is 33 students for experimental class and 36 students for control class. The improvement is calculated by using N-Gain. The data analysis uses T-Test. The research result show that the student pre-ability of mathematical communication for experimental and control class is equal. The students post-ability of mathematical communication for experimental class is higher than the students who is applied by conventional technique. Therefor, the implementation of Giving Question and Getting Answer technique can improve the students mathematical communication ability for grade VIII SMP Negeri 1 Cinangka.